Pengaruh Disiplin Kerja Terhadap Kinerja Pegawai Pada Dinas Kehutanan Provinsi Sulawesi Selatan - Elieser Ebong; Azhari Ismail; Baharuddin Baharuddin (POLITEKNIK KETENAGAKERJAAN, 2023)
The purpose of his research was to provide how interpersonal conflict and workload affect how work stress at the South Sulawesi Provincial Forestry Service was surveyed to obtain primary data. Saturated sampling was used in the study, and a total of 54 people were sampled. The validity and reliability of these findings have been evaluated, through heteroscedasticity, multicollinearity, and normality tests have all been considered. The data analysis method uses simple regression.